Consistency of personal identity as a resource of pedagogical prevention of adolescents’ radicalization - Belov, Vasily (2020)
The article discusses the problem of countering the radicalization of adolescents. It is assumed that adolescents are a social group that is subject to radical influence. This paper emphasizes the growing tendency to involve adolescents and young men in extremist and terrorist acts. Modern theoretical concepts of radicalization are considered and their specific nature is determined. It is noted that all concepts take into account the role of disturbed or difficult social relationships as a latent factor of radicalization.